2017
DOI: 10.1038/srep46041
|View full text |Cite
|
Sign up to set email alerts
|

Serum glycopattern and Maackia amurensis lectin-II binding glycoproteins in autism spectrum disorder

Abstract: The pathophysiology of autistic spectrum disorder (ASD) is not fully understood and there are no diagnostic or predictive biomarkers. Glycosylation modified as many as 70% of all human proteins can sensitively reflect various pathological changes. However, little is known about the alterations of glycosylation and glycoproteins in ASD. In this study, serum glycopattern and the maackia amurensis lectin-II binding glycoproteins (MBGs) in 65 children with ASD and 65 age-matched typically developing (TD) children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…These principles are consistent with previous research. These criteria are in keeping with previous report 20.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…These principles are consistent with previous research. These criteria are in keeping with previous report 20.…”
supporting
confidence: 76%
“…The structures of epoxy-coated, hydroxyl-functionalized magnetic particles and GMPCs were determined by using infrared spectroscopy (FT-IR-spectrometer; Nicolet 5700, Thermo electron Corporation). [18][19][20]…”
Section: Preparation Of Gmpcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereinto, OSTC, MAN1B1 and MGAT5, translating to key enzymes for N-linked glycosylation, were signi cantly down-regulated in ASD. In our previous study, we found a signi cant decrease of STL binding glycans or glycoproteins that contain trimers and tetramers of GlcNAc (core structure of N-glycans) in ASD versus in TD (fold change = 0.54, p = 0.0057) [10]. In all, no matter at the gene level, the transcription level, or the level of translation and post-translation modi cation, abnormalities of glycosylation and carbohydrate metabolism might be an important molecular mechanism of ASD.…”
Section: Discussionmentioning
confidence: 87%
“…In recent years, blood/serum biomarkers have drawn much attention due to their accessibility, low cost and rapid detection. In our previous study, we identi ed four candidate peptides as biomarkers, namely SerpinA5-A, ApoC1-A, FABP1-A and PF4-A [9], and α2-3-linked sialylation of apolipoprotein D (APOD) [10] as potential biomarkers for ASD. A recent study also showed that SLC25A12, LIMK1, and RARS might serve as potential blood protein biomarkers for ASD [11].…”
mentioning
confidence: 99%